The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0194988
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathology predicts infantile physical development during first 18 months in Japanese population: Hamamatsu birth cohort for mothers and children (HBC Study)

Abstract: The present study aimed to investigate the relationship between placental pathological findings and physiological development during the neonate and infantile periods. Study participants were 258 infants from singleton pregnancies enrolled in the Hamamatsu Birth Cohort for Mothers and Children (HBC Study) whose placentas were stored in our pathological division. They were followed up from birth to 18 months of age. Physiological development (body weight and the ponderal index [PI]) was assessed at 0, 1, 4, 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 39 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…Extensive efforts have been made over the past few decades to establish effective biomarkers through the application of ‘omics’ technologies, which may identify individuals at high risk of developing NCDs; however, only a very small number have been translated into routine health care support 39 , 40 . The present study revealed that some placental pathological findings were associated with changes in infantile neurodevelopment, in addition to our previous findings on body weight and body composition 27 in the Japanese population, suggesting that placental pathological findings are applicable as a type of biomarker for predicting neuronal as well as physical development after birth. Follow-up investigations of the offspring of the present participants are now ongoing.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Extensive efforts have been made over the past few decades to establish effective biomarkers through the application of ‘omics’ technologies, which may identify individuals at high risk of developing NCDs; however, only a very small number have been translated into routine health care support 39 , 40 . The present study revealed that some placental pathological findings were associated with changes in infantile neurodevelopment, in addition to our previous findings on body weight and body composition 27 in the Japanese population, suggesting that placental pathological findings are applicable as a type of biomarker for predicting neuronal as well as physical development after birth. Follow-up investigations of the offspring of the present participants are now ongoing.…”
Section: Discussionsupporting
confidence: 81%
“…After weighing and an examination of gross morphology, whole placentas were stored in our pathological division after being vacuum-sealed in plastic packages with 10% formaldehyde (0.1 M sodium citrate buffer, pH 7.4). Seven paraffin blocks were systematically obtained from each placenta for the pathological examination by systematic random sampling, as previously described 18 , 19 , 27 . In brief, 5-mm-wide linear parallel slices of placental tissue were cut at an interval of approximately 3 cm perpendicular to the greatest dimension of the placental axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three researchers (Y.H., N.I., and M.M.) macroscopically evaluated 5,201 placentas delivered at Hamamatsu University Hospital between April 2010 and March 2017, among which 1380 placentas were pathologically examined according to the criteria of S1 Table as previously described [ 15 ]. Written informed consent was obtained from the participating parturient during pregnancy after a full explanation of the study.…”
Section: Methodsmentioning
confidence: 99%
“…After they had been weighed and their gross morphology examined, whole placentas were stored in our pathological division after being vacuum-sealed in plastic packages with 10% formaldehyde, as described previously. Seven paraffin blocks were systematically obtained from each placenta for the pathological examination by systematic random sampling as previously described [ 15 ]. Two rolls of extraplacental membranes per placenta were together embedded in a block to make a single section.…”
Section: Methodsmentioning
confidence: 99%